Leadership Roles and Early Christian Communities - Osiek, Carolyn 1940- (2019)
This essay analyzes evidence for leadership roles of women in early Christianity. Gendered cultural constraints were necessarily at play from the beginning and throughout the development and enactment of leadership structures. Yet women found ways to exercise leadership in a milieu of intertwined and pervasively patriarchal and androcentric cultures—Greek, Jewish, and Roman. The essay argues that any notion of linear development in either direction, toward the “liberation” of women or toward their containment and subordination, does not seem warranted. Rather, the dynamics of both “liberation” and “oppression” and everything in between are to be seen at every level and in every historical period. It explores early Christian women’s roles in the household, in the assembly, as apostles, prophets, and teachers, as martyrs, and as widows and deacons.